Paper moon eaudiobook - Windsor, Linda (Moonstruck, 2015)
Linda Windsor is an award-winning author of whimsical romantic tales with Christian messages. Caroline Spencer is starting to regret agreeing to chaperon her daughter's high school class on their trip to Mexico. But another single parent, Blaine Madison, has a resemblance to Harrison Ford that is making her feel a little better. The fun comes to a halt, though, when their daughters get accidentally caught up in a smuggling ring.